THE DEVELOPMENT OF INDIAN MULTINATIONAL- A CASE STUDY OF TATA GROUP - Garg, Ankit Garg (2010)
In the current scenario as there is huge competition between domestic companies as well as multinational companies so survive in this situation its necessary to develop Indian multinational companies in foreign market to promote and achieve strategic growth. When they have multinationals entered into foreign market organization’s growth and development totally depends on certain issues like integration of supply chain network, cultural barriers and use of information technology in business communication